2022
DOI: 10.3390/jmse10020202
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Near-Inertial Waves Induced by Typhoon Mitag (2019) on the Southwestern East China Sea Continental Slope

Abstract: Based on horizontal velocity data recorded by a moored acoustic Doppler current profiler (ADCP) deployed on the southwestern continental slope of the East China Sea (ECS), this study investigates the characteristics of near-inertial waves (NIWs) induced by typhoon Mitag in October 2019. The results indicated that Mitag-induced near-inertial kinetic energy (NIKE) was mainly concentrated above 290 m and was subsurface-intensified; both the maximum velocity and kinetic energy of the NIWs occurred at a depth of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
(124 reference statements)
1
4
0
Order By: Relevance
“…Moreover, prominent spectral densities appear around the frequencies of 0 and M 2 throughout the observation depth layer. For the local internal wave field, the D2 ITs overwhelm other internal wave signals, which is consistent with previous studies [23,29,32,36]. The spectral densities of D1 ITs are only less than those of the D2 ITs.…”
Section: Spectral Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, prominent spectral densities appear around the frequencies of 0 and M 2 throughout the observation depth layer. For the local internal wave field, the D2 ITs overwhelm other internal wave signals, which is consistent with previous studies [23,29,32,36]. The spectral densities of D1 ITs are only less than those of the D2 ITs.…”
Section: Spectral Analysissupporting
confidence: 91%
“…At the mooring, nonlinear interactions between internal waves occurred because of spectral peaks that appeared at the MO 3 , MK 3 , M 4 , and MS 4 frequencies. Although the near-inertial frequency shows the characteristic of broadband, when significant near-inertial waves occur at the mooring, such as that induced by the passage of a typhoon, a spectral peak will appear near the local inertial frequency (f ) [23].…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…29°N is the critical latitude for the PSI of the semidiurnal internal tides (Ansong et al., 2018; MacKinnon et al., 2013), which is consistent with the location of our study region and the predominant M 2 semidiurnal tide here. Besides, the occurrence of PSI has been observed in the ECS (Yang et al., 2020) and has been examined under typhoon conditions (Ouyang et al., 2022). We concluded that the PSI, as well as strengthened near‐inertial mixing and tidal mixing during Chan‐hom, contributed to the algal bloom by mixing KSSW into the upper layer.…”
Section: Discussionmentioning
confidence: 99%
“…The damage caused by disasters is increasing worldwide, with hundreds of thousands of deaths due to the occurrence of complex large-scale disasters such as the 2011 Fukushima nuclear disaster [1,2], the 2010 Haiti earthquake [3,4], and the 2004 Indian tsunami [5]. South Korea has also experienced human casualties and property damage caused by large-scale disasters in the past 10 years, such as typhoon Mitag [6] in 2009, the hydrofluoric acid spill accident in Gumi [7] in 2013, and the collapse of the Mauna Ocean Resort gymnasium [8] and sinking of the motor vessel Sewol [9] in 2014. Such damage is aggravated due to poor disaster response.…”
Section: Introductionmentioning
confidence: 99%